Internal tooth bleaching: a review - Portillo, Fernando Rosas López; Urias, Aurea Elizabeth Valle; Arredondo, Tonantzin González; Valenzuela, Jesus Gamez; Guerrero, Felix Manuel Manjarrez; Angulo, Ingryd Fabiola Molina; Quintero, Enedina Duarte; Santos, Patricia Medina; Urióstegui, Cristhal Duque; Treviño, Alan I. Valderrama (International Surgery Journal, 2025)
Intracoronal bleaching is a conservative, cost-effective aesthetic procedure designed to enhance the color of non-vital teeth over an extended period. The selection of bleaching agents, application methodologies, and comprehension of biological interactions with both soft and hard tissues are pivotal for achieving immediate treatment success. Presently, bleaching agents predominantly utilize peroxide-releasing compounds in diverse formulations applied to enamel and dentin. This review aims to provide a comprehensive overview of key aspects of intracoronal bleaching, including primary adverse effects and considerations essential for optimizing treatment efficacy.